(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, 3 varieties of artichoke (Cynara scolymus L.) were identified and the amount of water-soluble vitamins and polyphenolic compounds in the dried leaves of the plant was studied using HPLC. The amounts of vitamins B1, B2, B3 B6, B9, C and some types of polyphenolic compounds, such as rutin, gallic acid, salicylic acid, quercetine and appegenin, found in plant leaves were compared.